The impact of stormwater biofilter design and operational variables on nutrient removal - a statistical modelling approach. (1st January 2021) - Zhang, Kefeng; Liu, Yizhou; Deletic, Ana; McCarthy, David T.; Hatt, Belinda E.; Payne, Emily G.I.; Chandrasena, Gayani; Li, Yali; Pham, Tracey; Jamali, Behzad; Daly, Edoardo; Fletcher, Tim D.; et al.
Highlights: Statistical models incorporating both design and operational parameters are developed. All models perform well in predicting biofilters outflow TP and TN concentrations. The results show the importance of not only design but also operational factors. Infiltration rate and inflow concentrations are key operational factors. The results enable us to consider operational factorsin biofilter design process. Abstract: Biofiltration systems can help mitigate the impact of urban runoff as they can treat, retain and attenuate stormwater. It is important to select the optimal design characteristics of biofilters (e.g., vegetation, filter media depth) to ensure high treatment performance. Operational conditions (e.g., infiltration rate) can also lead to significant changes in biofilter treatment performance over time. The impact of specific operational conditions on water quality treatment performance of stormwater biofilters is still not well understood. Furthermore, despite the importance of design characteristics and operational conditions on biofilter treatment performance, there is a lack of models that can be used to determine the optimal design and operation. In this paper, we developed a series of statistical models to predict the Total Phosphorus (TP) and Total Nitrogen (TN) removal performance of stormwater biofilters using various numbers of design characteristics and operational conditions. These statistical models were tested using data collected from four extensive laboratory-scale biofilter column studies. It was found that all models performed relatively well with a Nash-Sutcliffe Efficiency (NSE) of 0.42 - 0.61 for TP and 0.37 - 0.63 for TN. The most important design characteristics were filter media type and depth for TP treatment, and vegetation type and submerged zone depth for TN treatment. In addition, infiltration rate and inflow concentrations were the operational conditions that greatly influence outflow TP and TN concentrations from stormwater biofilters. As such, these variables need to be carefully considered when designing and operating stormwater biofilters. Sensitivity analysis results indicate that the model was quite sensitive to all regression coefficients and intercepts. Additional modelling exercises show that the model could be further simplified by reducing the number of cross-correlated parameters. These models can be used by practitioners for not just optimising the design, but also operating biofilters using real-time monitoring and control to achieve optimum performance. Graphical abstract: Image, graphical abstract